Domain-Swap Dimerization of Acanthamoeba castellanii CYP51 and a Unique Mechanism of Inactivation by Isavuconazole - Sharma, Vandna; Shing, Brian; Hernandez-Alvarez, Lilian [UNESP]; Debnath, Anjan; Podust, Larissa M. (Amer Soc Pharmacology Experimental Therapeutics, 2020)
Cytochromes P450 (P450, CYP) metabolize a wide variety of endogenous and exogenous lipophilic molecules, including most drugs. Sterol 14 alpha-demethylase (CYP51) is a target for antifungal drugs known as conazoles. Using X-ray crystallography, we have discovered a domain-swap homodimerization mode in CYP51 from a human pathogen, Acanthamoeba castellanii CYP51 (AcCYP51). Recombinant AcCYP51 with a truncated transmembrane helix was purified as a heterogeneous mixture corresponding to the dimer and monomer units. Spectral analyses of these two populations have shown that the CO-bound ferrous form of the dimeric protein absorbed at 448 nm (catalytically competent form), whereas the monomeric form absorbed at 420 nm (catalytically incompetent form). AcCYP51 dimerized head-to-head via N-termini swapping, resulting in formation of a nonplanar protein-protein interface exceeding 2000 angstrom 2 with a total solvation energy gain of -35.4 kcal/mol. In the dimer, the protomers faced each other through the F and G a-helices, thus blocking the substrate access channel. In the presence of the drugs clotrimazole and isavuconazole, the AcCYP51 drug complexes crystallized as monomers. Although clotrimazole-bound AcCYP51 adopted a typical CYP monomer structure, isavuconazole-bound AcCYP51 failed to refold 74 N-terminal residues. The failure of AcCYP51 to fully refold upon inhibitor binding in vivo would cause an irreversible loss of a structurally aberrant enzyme through proteolytic degradation. This assumption explains the superior potency of isavuconazole against A. castellanii. The dimerization mode observed in this work is compatible with membrane association and may be relevant to other members of the CYP family of biologic, medical, and pharmacological importance. SIGNIFICANCE STATEMENT We investigated the mechanism of action of antifungal drugs in the human pathogen Acanthamoeba castellanii. We discovered that the enzyme target [Acanthamoeba castellanii sterol 14 alpha-demethylase (AcCYP51)] formed a dimer via an N-termini swap, whereas drug-bound AcCYP51 was monomeric. In the AcCYP51-isavuconazole complex, the protein target failed to refold 74 N-terminal residues, suggesting a fundamentally different mechanism of AcCYP51 inactivation than only blocking the active site. Proteolytic degradation of a structurally aberrant enzyme would explain the superior potency of isavuconazole against A. castellanii.